International census and population trends for Bewick’s Swans Cygnus columbianus bewickii wintering from the East Mediterranean to Central Asia - Rees, Eileen C.; Rozenfeld, Sonia; Vangeluwe, Didier; Ioannidis, Panagiotis; Erciyas-Yavuz, Kiraz; Belousova, Anna; Rustamov, Eldar; Solokha, Alexander; Sultanov, Elchin; Kowallik, Christine; Portolou, Danae; Khrokov, Artyom; et al. (Wildfowl, 2024)
Trends in abundance and changes in the distribution of the Northeast Europe/ Northwest Europe Bewick’s Swan Cygnus columbianus bewickii population have been studied in detail since the second half of the 20th century, but much less is known about the Northwestern Siberia/Caspian population which was estimated at 1,000–1,500 individuals at the turn of the century. Here, we describe the results of the first species-specific mid-winter International Bewick’s Swan Census (IBSC) covering the East Mediterranean to Central Asia, made in January 2020. We also use longer-term data collated by Wetlands International through the annual International Waterbird Census (IWC) programme to construct trends in wintering numbers in the region. Results from the IBSC and IWC both showed a marked increase in population size for the Northwestern Siberia/Caspian Bewick’s Swans over the past two decades. A total of 6,819 was recorded during the IBSC and there was a five-year mean of 9,111 ± 4,300 swans reported to the IWC (for the years 2018–2022) with a peak count of 13,775 in 2019. An aerial survey of the Volga Delta in the northern Caspian Sea in 2020, rarely covered because of the logistical difficulties of carrying out mid-winter counts in the region, found an estimated 551 Bewick’s Swans wintering at the site. There was marked annual variation in the IWC counts recorded from 2017 onwards, although the reasons for these fluctuations remain unknown. Trends analysis suggested a slow increase over time from 2000–2015, followed by a period of rapid increase during 2015–2017, then a weak decline in 2017–2022. Given that the IBSC and the IWC have provided totals of > 6,000 Bewick’s Swans in five of the last six years, however, we propose that the new population estimate should be increased to 6,000–13,000 birds, pending further comprehensive surveys of the whole region.